2020
DOI: 10.3389/fimmu.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

In utero Exposure to Maternal Chronic Inflammation Transfers a Pro-Inflammatory Profile to Generation F2 via Sex-Specific Mechanisms

Abstract: Generational transfer of maladaptations in offspring have been reported to persist for multiple generations in conditions of chronic inflammation, metabolic and psychological stress. Thus, the current study aimed to expand our understanding of the nature, potential sex specificity, and transgenerational plasticity of inflammatory maladaptations resulting from maternal chronic inflammation. Briefly, F1 and F2 generations of offspring from C57/BL/6 dams exposed to a modified maternal periconception systemic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In line with this result, maternal LPS-stimulated inflammation in rodents determined a proinflammatory macrophage phenotype and enhanced IL-1 β production in adult progeny under immune challenge [ 84 ]. Moreover, a recent animal model of chronic LPS-induced maternal inflammation found sex-specific leukocyte glucocorticoid hypersensitivity and exaggerated inflammatory cytokine responses in two generations of progeny [ 91 , 92 ]. In a mouse model, despite a comparable birth weight, a maternal high-fat diet and normal diet were shown to be associated with inflammatory changes in the adipose tissue of the offspring, including increased chemokine and cytokine expression [ 85 ].…”
Section: Maternal Obesity-related Inflammation and Developmental Pmentioning
confidence: 99%
“…In line with this result, maternal LPS-stimulated inflammation in rodents determined a proinflammatory macrophage phenotype and enhanced IL-1 β production in adult progeny under immune challenge [ 84 ]. Moreover, a recent animal model of chronic LPS-induced maternal inflammation found sex-specific leukocyte glucocorticoid hypersensitivity and exaggerated inflammatory cytokine responses in two generations of progeny [ 91 , 92 ]. In a mouse model, despite a comparable birth weight, a maternal high-fat diet and normal diet were shown to be associated with inflammatory changes in the adipose tissue of the offspring, including increased chemokine and cytokine expression [ 85 ].…”
Section: Maternal Obesity-related Inflammation and Developmental Pmentioning
confidence: 99%
“…In this regard, food, exercise, and an enriched environment are considered as positive modulators [20,[43][44][45], while neuroinflammation, infections, and ageing have been proposed as negative regulators [15,[46][47][48]. Several studies have reported a characteristic age-associated decrease in Gdnf gene expression patterns in different rodent strains [49][50][51]. Consistent with these findings, the current results showed that ageing significantly affected the expression of both Gdnf and GFRα1 genes in CD-1 mice, with lower expression detected in 15-months-old relative to 3-months-old mice.…”
Section: Accelerated Age-associated Decline In Hippocampal Gdnf/gfrα1...mentioning
confidence: 99%
“…In animal models, adverse conditions in the uterus during germline programming may be transmitted through both paternal and maternal lines to induce disease phenotypes in offspring or even be inherited in multiple generations (Constantinof et al, 2016 ; Coley et al, 2019 ). Studies have revealed that the effects of chronic gestational inflammation on proinflammatory phenotype could be transmitted to F1 offspring and, to some extent, F2 offspring (Adams and Smith, 2019 , 2020 ). Anxiety-like behaviors increase with age in rodents, for instance in Kunming, C57BL, and SAMP8 mice and rats (Chen et al, 2004 ; Schulz et al, 2007 ; Penteado et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%